2014
DOI: 10.1111/jan.12380
|View full text |Cite
|
Sign up to set email alerts
|

Differences in methodological quality between positive and negative published clinical trials

Abstract: Potential differences in methodological quality between positive and negative trials may lead to positive trials with biased results, or discrimination against negative trials. The CONSORT is recommended, but use is still limited. Therefore, it is important to reinforce the use of these guidelines to supply readers with information on the quality of the published trials. The combination of authors publishing higher quality trials and deeper reader knowledge of quality assessment can have important clinical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…This is in contrast to a recent paper that reviewed studies published in nursing journals in which investigators found significantly higher level of methodological quality for negative studies. 26 Nevertheless, the authors also reported that positive studies were published more frequently than negative studies (73.6% vs 26.4%), in line with our results. The uneven distribution of positive and negative studies was similar among observational and RCT cohort in our study.…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast to a recent paper that reviewed studies published in nursing journals in which investigators found significantly higher level of methodological quality for negative studies. 26 Nevertheless, the authors also reported that positive studies were published more frequently than negative studies (73.6% vs 26.4%), in line with our results. The uneven distribution of positive and negative studies was similar among observational and RCT cohort in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Two well-trained independent reviewers evaluated the quality of RCTs using the Jadad Quality Score (Chiavetta, Martins, Henriques, & Fregni, 2014;Jadad et al, 1996) and Cochrane RoB 2.0 (Eldridge et al, 2016). The reviewers examined the quality of trails using the Jadad Quality Score based on three aspects: randomization, double blinding, and reasons for patient dropout/loss to follow-up.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The publications reporting in favour of IHC were more likely to have uncertain/high risk of bias ratings across most domains than publications reporting no differences between groups, or effects in favour of usual care. While low methodological quality may be associated with larger estimates of treatment effect in some disciplines and disease areas, this phenomenon is not universal . As such, the degree to which this phenomenon applies to IHC research requires further exploration.…”
Section: Discussionmentioning
confidence: 99%